Mycorrhiza stimulates root-hair growth and IAA synthesis and transport in trifoliate orange under drought stress - Liu, Chun-Yan; Zhang, Fei; Zhang, De-Jian; Srivastava, A K; Wu, Qiang-Sheng; Zou, Ying-Ning (Scientific reports, 2018)
Root-hair growth and development regulated by soil microbes is associated with auxin. In this background, we hypothesized that mycorrhizal fungal inoculation induces greater root-hair growth through stimulated auxin synthesis and transport under water stress conditions. Trifoliate orange (Poncirus trifoliata) was inoculated with an arbuscular mycorrhizal (AM) fungus (Funneliformis mosseae) under well-watered (WW) and drought stress (DS) for 9 weeks. Compared with non-AM seedlings, AM seedlings displayed significantly higher density, length, and diameter of root hairs and root indoleacetic acid (IAA) level, whereas lower total root IAA efflux, regardless of soil moisture status. Root PtYUC3 and PtYUC8 involved in IAA biosynthesis were up-regulated by mycorrhization under WW and DS, whereas AM-modulated expression in PtTAA1, PtTAR2, PtYUC4, and PtYUC6 depended on status of soil moisture. Mycorrhizal inoculation down-regulated the transcript level of root auxin efflux carriers like PtPIN1 and PtPIN3, whereas significantly up-regulated the expression of root auxin-species influx carriers like PtABCB19 and PtLAX2 under DS. These results indicated that AMF-stimulated greater root-hair growth of trifoliate orange under DS that is independent on AMF species is related with mycorrhiza-modulated auxin synthesis and transport, which benefits the host plant to enhance drought tolerance.
Keywords: Mycorrhizae; RNA, Messenger; Genes, Plant; Glomeromycota; Colony Count, Microbial; Droughts; počet mikrobiálních kolonií; kyseliny indoloctové; Plant Proteins; regulace genové exprese u rostlin; Stress, Physiological; biologický transport; Indoleacetic Acids; Gene Expression Regulation, Plant; Poncirus; rostlinné geny; mykorhiza; fyziologický stres; messenger RNA; Biological Transport; období sucha; rostlinné proteiny